Genetic variability and association mapping for yield and yield-related traits in African yam bean [Sphenostylis stenocarpa (Hochst ex. A. Rich) Harms] - Olomitutu, O.E. (University of Ibadan, 2023)
African Yam Bean (AYB) is an underutilised legume producing tubers and seeds rich in dietary proteins and minerals, but its Seed Yield (SY) is low. Landraces of AYB are repositories for potential beneficial alleles for the development of varieties with enhanced yield and qualities. However, limited information is available on the extent of genetic variation within available AYB landraces, the genetic basis of the variations and relative importance of SY-related traits, which are required for the development of varieties with improved SY and agronomic characteristics. Hence, genetic variability among some AYB accessions for SY and association of genomic regions with the yield-related traits were assessed. One hundred and ninety-six AYB accessions were evaluated for two years at Ibadan, Kano and Ubiaja following standard practices. The experimental design was 14×14 lattice with three replicates. Data were collected on Days to Pod Maturity (DPM), Pod Weight (PDW), Pod Length (PL), Seed Length (SL), Shelling Percentage (SP), 100-Seed Weight (HSW), Seeds Per Pod (SPP) and Seed Thickness (ST), while SY was estimated. Data were subjected to principal component analysis, cluster analysis, correlation analysis, path coefficient analysis, descriptive statistics and ANOVA at α0.05. Estimates of variance components, Genotypic Coefficient of Variation (GCV), Phenotypic Coefficient of Variation (PCV) and broad-sense heritability were computed for the traits. Yield stability index was used to identify superior and stable accessions. The 196 accessions were genotyped using 5,416 DArTseq-based Single Nucleotide Polymorphism (SNP) markers, from which 2,491 markers and 195 accessions were retained after quality filtering. Marker-trait associations were determined using the mixed linear model. Accessions, environments and accession×environment interaction effects were significant for all the traits. The DPM ranged from 118.5±14.3 (TSs-8, Ubiaja) to 220.0±6.0 (TSs-59, Kano), PW ranged from 4.2±0.3 g/plant (138A, Kano) to122.7±17.6 (TSs-421, Ibadan), while PL was shortest in accession TSs-22B (12.0±1.3 cm, Kano) and longest in TSs-51 (27.3±0.6 cm, Ibadan). The SY ranged from 1.3±0.1 (TSs-326, Kano) to 77.6±10.4 g/plant (TSs-421, Ibadan). Variances due to environment and accession×environment interaction were higher than the genotypic variance for all the traits. Also, estimates of PCV were higher than GCV for all traits. Broad-sense heritability ranged from 17.1±3.5% (DPM) to 66.4±0.2% (SL). The first three principal components accounted for 59.7% of the total variation among the accessions. Five major clusters were delineated based on phenotypic characteristics. Shelling percentage (rg=0.76), 100-SW (rg=0.29), DPM (rg=0.45), PW (rg=0.89), SPP (rg=0.20) and ST (rg=0.41) had significant genetic correlations with SY, and exhibited positive direct effects on SY. Accessions TSs-119, TSs-101, 138A, TSs-4, TSs-157A and TSs-61 were identified as superior and stable. Across locations, 24 SNP markers were significantly associated with the traits at a threshold of –log (p) =4, and explained 7.1 to 12.8% of the phenotypic variation among the accessions. A wide genetic variation exists among the African yam bean accessions. Selection criteria for improved seed yield in African yam bean should include shelling percentage, 100-seed weight, days to pod maturity, pod weight, seeds per pod and seed thickness.